(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The article is based on archaeological materials and is devoted to the study of artistic metal products of Khorezm during the renaissance period. In Khorezm, under the influence of Islamic art of the 10th-11th centuries, the tradition of decorating artistic metal and forms of artistic objects increased , processing techniques and peculiar traditions in their decoration appeared. At the beginning of the XII-XIII centuries, the production of artistic metal products reached a high level. Artistic metal objects of that time bear stylized images of animals (rabbits, beetroots). Also at the same time, the production of zoomorphic artistic metal products will be launched. Of these, items in the form of birds and horses were found in the monuments.